Too Much Glue - Lefebvre, Jason (Children's librarian); Retz, Zac (Brooklyn, NY : Flashlight Press, 2013)
"Matty LOVES glue. At home with Dad, he makes glue glasses, glue mustaches, and glue bouncy balls. But at school, Matty's art teacher worries and warns, 'Too much glue never dries.' In art class one day, Matty decides to make the most fantastic glue project ever, with a super-special ingredient -- himself!" -- from publisher's web site.
Keywords: Glue -- Juvenile fiction; Schools -- Juvenile fiction; Glue -- Fiction; Schools -- Fiction